Assessing Usability Elements For A Website of Higher Education Website - Nur Sukinah, Aziz; Adzhar, Kamaludin; Norrozila, Sulaiman (2013)
Nowadays, humans are inseparable with the internet. Most of the desired information can be obtained easily by just at fingertips. Web sites are widely used in daily life no matter for work or for entertainment, and connect with others in their social life. Usability is one of the quality factors that determine the successfulness of a website. This study reviews existing usability standards and model from previous study. Based on the study, many previous works only mentioned the attribute in usability in general and did not include sub-attribute. There also did not much published works in usability guidelines that comes up with metric for easy measurement especially focusing for website. This study identifies the major aspects in website usability and forming a useful guideline that include accessibility in website usability unlike earlier work which separate between usability and accessibility